2018
DOI: 10.5005/jp-journals-10005-1552
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Clinical Evaluation of Resin-based Pit and Fissure Sealant and Self-adhering Flowable Composite: An In Vivo Study

Abstract: AimThe study evaluated the use of self-adhering flowable composite as a fissure sealant and compared it with a resin-based pit and fissure sealant.Materials and methodsForty children were selected for the study and all their four permanent first molars were subjected to fluoride free pumice oral prophylaxis. Their occlusal fissures were then prepared with fissurotomy bur using high-speed handpiece under cotton roll isolation and low volume suction. Simple random sampling was done and accordingly a child either… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 13 publications
2
10
0
Order By: Relevance
“…In the RB group, 75.7%, 54.1%, and 37.8% of sealants were affected, respectively, and these percentages were greater than those in the RB group at all follow-up times, especially at 12 months. Wadhwa et al reported (2018) [15] that the marginal integrity rate of self-adhering owable composite (Dyad ow) as a sealant was better than that of RB (Helioseal-F), which further supported our ndings. In a study by ElEmbaby et al ( 2019), the marginal integrity of the self-adhering owable composite (Fusio liquid Dentin) was high at the 6-, 12-, and 24-month follow-ups, which is consistent with the results of the present study [19].…”
Section: Discussionsupporting
confidence: 89%
“…In the RB group, 75.7%, 54.1%, and 37.8% of sealants were affected, respectively, and these percentages were greater than those in the RB group at all follow-up times, especially at 12 months. Wadhwa et al reported (2018) [15] that the marginal integrity rate of self-adhering owable composite (Dyad ow) as a sealant was better than that of RB (Helioseal-F), which further supported our ndings. In a study by ElEmbaby et al ( 2019), the marginal integrity of the self-adhering owable composite (Fusio liquid Dentin) was high at the 6-, 12-, and 24-month follow-ups, which is consistent with the results of the present study [19].…”
Section: Discussionsupporting
confidence: 89%
“…The review showed that the main self-adhesive flowable resins evaluated were Vertise Flow (Kerr Corporation, Orange, CA, USA) [1,2,[15][16][17][18], and Fusio Dentin Liquid (Pentron Clinical, Orange, CA, USA) [19][20][21], Self-adhesive Bulk Fill Restorative (3M Oral Care, St Paul, MN, USA) [21], Filtek Supreme Ultra Flowable (3M ESPE, USA) [22], and Constic (DMG; Hamburg, Germany) [3].…”
Section: Discussionmentioning
confidence: 99%
“…This review assessed five distinct commercial brands of self-adhesive flowable composite resins (Table 2). Among the studies included, Vertise Flow resin (Kerr Corporation, Orange, CA, USA) was evaluated in six studies [1,2,[15][16][17][18], while Fusio Dentin Liquid (Pentron Clinical, Orange, CA, USA) was examined in three [19][20][21]. Additionally, one study investigated Selfadhesive Bulk Fill Restorative (3M Oral Care, St Paul, MN, USA) [22], another focused on Filtek Supreme Ultra Flowable (3M ESPE, USA) [23], and Constic (DMG; Hamburg, Germany) was analyzed in a separate study [3].…”
Section: Descriptive Analysismentioning
confidence: 99%
See 2 more Smart Citations